ANALISIS LAHAN KRITIS DAN RENCANA PENATAAN LAHAN DI DAEREH ALIRAN SUNGAI (DAS) BAUBAU - Inal Karizal; La Baco Sudia; Sahindomi Bana (Jurnal Perencanaan Wilayah, 2020)
The purpose of this study is 1) to identify changes in land use through the interpretation of Landsat imagery from 2007 to 2017 in the Baubau watershed and 2) to analyze the critical level of land and land use planning through land rehabilitation techniques and land conservation. The level of critical land was analyzed based on Scoring through GIS using four types of data, namely Landsat 2017 imagery, scoring standards for critically protected forest areas, protected areas outside the forest area and cultivation areas for agricultural business. The land use plan is based on the 2017 land capability and land cover classes that are overlaid with the use zone (Space Pattern) using the ArGis 10.3 application. The results showed changes in land cover / use from 2007 to 2017 i.e. secondary dryland forests with an area of 2,830.2 ha turned into shrubs, open land, mixed bush dryland agriculture, dry land agriculture and plantations with an area of 756.77 ha (26.74%) . Plantations with an area of 814.06 ha are turned into open land, dry land mixed with bush farming and 34.17 ha (4.20%) of settlements. Shrub land with an area of 1,196.77 ha has been turned into secondary dryland forest, open land, mixed-bush dry land agriculture, dry land agriculture and plantation with an area of 717.71 ha (59.97%). Bush mixed dryland agriculture with an area of 442.73 ha turned into secondary dryland forest, open land, settlements and plantations with an area of 99.58 ha (22.49%). Dry land agriculture with an area of 1,336.3 ha has been transformed into secondary dryland forest, shrubland, mixed shrub agriculture and plantation with an area of 370.81 ha (27.75%). Rice fields with an area of 200.91 ha are plantations and settlements with an area of 8.84 ha (4.40%). Savana with an area of 165.38 ha turned into a settlement of 7.72 ha (4.67%). While the open land with an area of 49.8 ha turned into secondary dryland forest, shrubs and plantations of 24.87 ha (49.94%). The results of the analysis of critical lands show that the Baubau watershed area with a rather critical category of 2,691.25 ha (33.62%), uncritically 2,564.76 ha (32.04%), critical potential 978.55 ha (12.23%), critical 674.61 ha (8.43%) and very critical 119.04 ha (1.49%). While the direction of land structuring is categorized into nine land cover / land use classes, namely secondary dry land forest with an area of 2,558.85 ha (31.97%), plantation 840.25 ha (10.50%), dry land agriculture 447.16 ha (5.59%), reforestation 929.47 ha (11.61%), reforestation 541.67 ha (6.77%), agroforestry 120.45 ha(1,50%), rice fields 172.10 ha(2,15%), partnership patterns 1,235.17 ha (15.43%)  and settlements covering 1,158.80 ha (14.48%).Key words : Babau watershed, Critical Land, Land Arrangement Plan